A Study on the Effectiveness of Linear and Non-Linear Models in Forecasting Area and Production of Potato in Himachal Pradesh - Sukhdeep Kaur; Ashu Chandel; RK Gupta; Pawan Kumar; Geeta Verma (Archives of Current Research International, 2025)
This study analyzed the trend in area and production of potato over a time period is important for understanding the past behavior and for future planning. The secondary data for study of area and production of potato from 1989-2024 were collected. Various statistical growth models viz. linear, quadratic, cubic, compound and power applied for area and production of potato in Himachal Pradesh. The study revealed that cubic model was found to best fitted model for production of potato and none model were found suitable for potato area. Highest value of CDVI for area is 9.65 and production is 7.79 which indicate the higher level of instability in which variable is more erratic and less area over time. The decreasing annual growth rate for potato area is 0.2 percent and 1.5 percent with respect to production of potato over the studied period of time using compound model.